2016
DOI: 10.1097/coc.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Standardized Uptake Value of Lymph Nodes on Survival for Stage III Non-small Cell Lung Cancer Treated With Definitive Concurrent Chemoradiotherapy

Abstract: SUVmax nodes <8 was the only prognostic factor of PFS, DMFS, and OS in our study. PET-CT scan at the time of diagnosis is useful in stratifying patients into favorable and unfavorable groups in stage III NSCLC treated with definitive concurrent chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Three size-related prognostic factors were found across 38 inclusions (Table 3): Tumor diameter [16,32,34,38,45,48-52,57,58 ,60,68,69,78,83], Tumor volume [16,18,66,67,71,73,80,81], and Gross Tumor Volume (GTV) [11,13,15,18,21,35,41,47,54,64,65,70,73,74,76,77,80]. Tumor volume and GTV were considered unique prognostic factors, as GTV encompasses both the volume of the primary tumor and involved lymph nodes [11,13,15,18,41,64,65], where tumor volume includes only primary tumor volume [13,16,66,67,71].…”
Section: Resultsmentioning
confidence: 99%
“…Three size-related prognostic factors were found across 38 inclusions (Table 3): Tumor diameter [16,32,34,38,45,48-52,57,58 ,60,68,69,78,83], Tumor volume [16,18,66,67,71,73,80,81], and Gross Tumor Volume (GTV) [11,13,15,18,21,35,41,47,54,64,65,70,73,74,76,77,80]. Tumor volume and GTV were considered unique prognostic factors, as GTV encompasses both the volume of the primary tumor and involved lymph nodes [11,13,15,18,41,64,65], where tumor volume includes only primary tumor volume [13,16,66,67,71].…”
Section: Resultsmentioning
confidence: 99%
“…The other 16 studies used multiple segmentation methods and the results of the studies were summarized in Table 3. Among the 16 studies, 11 studies evaluated the predictive value of MTV [23,[52][53][54][55][56][57][58][59][60][61]. Seven studies showed comparable predictive value between the different segmentation methods.…”
Section: Comparison Of the Fdg Pet Tumor Segmentation Methodsmentioning
confidence: 99%
“…From the view of tumor cell metabolic capacity, high standard uptake value (SUV max) of the tumor area may be related to poor survival among stage I to III disease. 6 , 7 Among patients who received anatomic resection and were identified as pathologic stage IIIA, pathologic tumor classification and mediastinal lymph node involvement have been identified as independent prognostic factors for disease-free survival. 8 In addition, patients without lymph node involvement or with lower metastatic lymph node ratio have been correlated to better survival.…”
Section: Introductionmentioning
confidence: 99%